2000
DOI: 10.1038/sj.ejcn.1601093
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing immunity by dietary consumption of a probiotic lactic acid bacterium (Bifidobacterium lactis HN019): optimization and definition of cellular immune responses

Abstract: Objective: To de®ne the cellular basis for immune enhancement by a probiotic lactic acid bacteria strain (Bi®dobacterium lactis HN019); and to determine whether immune enhancement can be optimized by delivery in oligosaccharide-enriched low-fat milk. Design: A double-blind, three-stage before-and-after intervention trial. Setting: Taipei Medical College Hospital, Taipei, Taiwan. Subjects: Fifty healthy Taiwanese citizens (age range 41 ± 81; median 60) randomly allocated to two groups. Interventions: In stage 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(85 citation statements)
references
References 26 publications
7
71
0
4
Order By: Relevance
“…Numerous studies dealing with the influence of probiotics on phagocytically active cells found corresponding results. For the strains L. rhamosus HN001, B. lactis HN019 and L. paracasei LTH 2579, it was shown to enhance the mononuclear leukocyte phagocytosis (Arunachalam et al, 2000;Chiang et al, 2000;Gill et al, 2001;Sheih et al, 2001;Jahreis et al, 2002). Indicating a stimulation of the immune system, these outcomes can be important for several population groups, for example elderly, stressed workers and children that are susceptible for infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies dealing with the influence of probiotics on phagocytically active cells found corresponding results. For the strains L. rhamosus HN001, B. lactis HN019 and L. paracasei LTH 2579, it was shown to enhance the mononuclear leukocyte phagocytosis (Arunachalam et al, 2000;Chiang et al, 2000;Gill et al, 2001;Sheih et al, 2001;Jahreis et al, 2002). Indicating a stimulation of the immune system, these outcomes can be important for several population groups, for example elderly, stressed workers and children that are susceptible for infections.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion to the intestinal mucosa and bacterial-epithelial-crosstalk are important criteria for exerting effects (Lu and Walker, 2001;Ouwehand et al, 2003). Numerous studies have shown an influence of probiotics on markers for the unspecific cellular immune response (Chiang et al, 2000;Gill et al, 2001;Sheih et al, 2001;Jahreis et al, 2002). Concerning specific cellular markers for immunity, the results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has already been shown that probiotics may lead to an increased IgA production [59] and stimulation of macrophage and NK activity [15,46]. Moreover, several studies have reported that probiotics are able to regulate both anti-and pro-infammatory cytokine production.…”
Section: Immunomodulationmentioning
confidence: 99%
“…Idosos que consumiram B. latis HN019 tiveram aumento na capacidade fagocítica dos leucócitos periféricos, através de estímulo por contato direto das LAB e frações extracelulares da parede celular bacteriana (KELLER et al, 1994;MIETTINEN et al, 1996) e na produção de citocinas, como o interferon-α; entretanto, continua incerto qual tipo celular é primeiramente influenciado pelo probiótico (CHIANG, 2000).…”
Section: Efeitos Benéficos Deunclassified